(untitled) (Marketing Journal, 2025)
This article provides a systematic analysis of the nature, forms, and effectiveness of international cooperation in the field of financial security. In the context of growing global economic integration and increasing transnational financial flows, the rol e of international organizations, financial institutions, and intergovernmental collaboration in ensuring national financial security is becoming increasingly important. The research explores key areas of international cooperation, including financial moni toring, combating financial crimes, risk assessment and management, and mechanisms for crisis prevention and resolution. The article also examines Uzbekistanʼs cooperation with major international financial institutions such as the International Monetary F und, the World Bank, and the Asian Development Bank, highlighting their role in strengthening the countryʼs financial resilience. Additionally, the paper addresses the challenges faced in international cooperation processes and offers evidence -based propos als for enhancing their effectiveness.